The prevalence and prognostic significance of Sarcopenia and Adipopenia in Pleural Mesothelioma - Andrew C. Kidd; Gordon W. Cowell; Geoffrey A. Martin; Jenny Ferguson; Dean A. Fennell; Matt Evison; Kevin G. Blyth (Cancer Treatment and Research Communications)
Introduction: Altered body composition is associated with adverse survival in multiple cancers. We determined the prevalence, prognostic significance and clinicopathological correlates of sarcopenia and adipopenia in Pleural Mesothelioma (PM) patients receiving chemotherapy. Methods: We performed a multi-centre retrospective cohort study. Clinical data and CT images were retrieved for 111 patients from 4 UK centres. Skeletal muscle (at L3 and T4) and fat tissue areas (at L3 only) were measured on pre- and post-chemotherapy CT scans (ImageJ software) and normalised for height. Pre-chemotherapy sarcopenia and adipopenia were defined using validated thresholds, where available or indices <25th percentile. Muscle/fat loss were defined by < 0 % change (%∆) between CT scans. Extreme muscle/fat loss were defined by <25th percentile of %∆. Overall survival associations were evaluated using Kaplan–Meier methodology ± Cox proportional hazards models. Results: T4 and L3 measurements were possible in 111/111 and 91/111 (82 %). L3 sarcopenia was observed at baseline in 35 % (32/91); all other features were observed in 25 % at baseline, as defined a priori. Body composition changes during chemotherapy were heterogeneous. Overall, 61.5 % and 53.1 % patients lost muscle at L3 and T4. 60.4 % lost fat (at L3 only). Extreme T4 muscle loss and total fat loss were independently prognostic (HR 2.99, p < 0.001; HR 1.92, p = 0.014). Pre-chemotherapy T4 muscle indices were inversely associated with age. No associations were observed with tumour volume, histology, weight, inflammatory markers. Conclusion: T4 muscle indices were feasible in all cases and outperformed L3 values in prognostication. Extreme T4 muscle and total fat loss were independently prognostic.